Qualities of a good university leader. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2013)
Within the recent decades, the globalising world has witnessed a growing trend in the development of higher education. Universities have become a driving force to ensure the future of nations and the universe (Topal, 2009). Whether public or private, large or small, universities are contributing to the development of societies through nurturing knowledge that provides societies with intellectual and cultural capital (Safakhah & Vaghari, 2012).